Contribution to the scintillation detection optimization in double phase detectors for direct detection of dark matter - Balan, Cătălin (2015)
Tese de doutoramento em Engenharia Física, ramo de Instrumentação apresentada à Faculdade de Ciências e Tecnologia da Universidade de Coimbra